Lauric Acid Is a Potent Biological Control Agent That Damages the Cell Membrane of Phytophthora sojae - Liang, Changhui; Gao, Wenteng; Ge, Ting; Tan, Xinwei; Wang, Jiayu; Liu, Huaxin; Wang, Yong; Han, Chao; Xu, Qian; Wang, Qunqing (Frontiers in Microbiology, 2021)
Sustainable management of plant pathogens is becoming more challenging, and novel solutions are needed. Plant biologically active secondary metabolites are important sources of novel crop protection chemistry. Effective individual compounds of these natural products have the potential to be successful new agrochemicals. In this study, we identified lauric acid (LA) from soybean defense leaf volatiles. LA inhibited the growth of Phytophthora sojae, the causal agent of soybean root rot. It influenced mycelial development, sporangium formation, and zoospore generation and germination by damaging the P. sojae cell membrane. Additionally, we showed that LA and several of its derivatives, such as glycerol monolaurate (GML), had similar biological activities. Both LA and GML were safe to soybean plants when used at less than 0.3 g a.i./plant and could promote soybean growth, implying their potential as eco-friendly biological control agents.